2022
DOI: 10.3390/su14053105
|View full text |Cite
|
Sign up to set email alerts
|

Developing Sustainable Careers during a Pandemic: The Role of Psychological Capital and Career Adaptability

Abstract: The Coronavirus disease 2019 (COVID-19) has not only had negative effects on employees’ health, but also on their prospects to gain and maintain employment. Using a longitudinal research design with two measurement points, we investigated the ramifications of various psychological and organizational resources on employees’ careers during the COVID-19 pandemic. Specifically, in a sample of German employees (N = 305), we investigated the role of psychological capital (PsyCap) for four career-related outcomes: ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 100 publications
(164 reference statements)
0
14
0
2
Order By: Relevance
“…The study included use of a questionnaire tool, and statistical tests were conducted to compute the differences between the samples. The deep learning technique was used to analyze students' perception if their learning environment Reference [34,35] developed a HEgame application, wherein the student's satisfaction was influenced by the application features that further impacted the prodeep learning approaches. The study concluded the fact that gamified applications impacted prodeep learning approaches, wherein students intended to expose their private learning-related information to their friends…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included use of a questionnaire tool, and statistical tests were conducted to compute the differences between the samples. The deep learning technique was used to analyze students' perception if their learning environment Reference [34,35] developed a HEgame application, wherein the student's satisfaction was influenced by the application features that further impacted the prodeep learning approaches. The study concluded the fact that gamified applications impacted prodeep learning approaches, wherein students intended to expose their private learning-related information to their friends…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…ResNet algorithm has been used in various domains. As an example, the study in [35] used ResNet classifier for the detection of specific language impairment (SLI) in children. The study proposed an automated approach to SLI detection using log-power spectra of speech samples.…”
Section: Resnet Algorithmmentioning
confidence: 99%
“…Regarding Profile 5, it is important to note that the role of LMX is not always robust, especially across contexts. For instance, a study by Zyberaj et al (2022) found no moderating role of LMX between PsyCap mechanisms and employees’ career adaptability during crises. As the authors note, “employees high in PsyCap have strong psychological resources that can facilitate their functioning in challenging environments (e.g., adaptability), even when there is a lack of social support” (p. 12).…”
Section: Discussionmentioning
confidence: 98%
“…Research showed that PsyCap could be relevant for many job-related outcomes, such as job satisfaction ( Zhang et al, 2021 ), innovation ( Dimas et al, 2022 ), and problem-solving ( Ho and Chan, 2022 ), as well as health performance, such as reducing emotional exhaustion ( Jung and Yoon, 2022 ) and increasing overall mental health ( Cao et al, 2022 ). Current findings have shown that PsyCap helps individuals deal with challenging environments, such as the COVID-19 crisis ( Alat et al, 2021 ; Zyberaj et al, 2022 ). For instance, Zyberaj et al (2022) found positive associations between PsyCap and career satisfaction and coping during the COVID-19 pandemic.…”
Section: An Applied Examplementioning
confidence: 95%
See 1 more Smart Citation